Positive and negative effects of COVID-19 pandemic on aquatic environment: a review - Ong, Meng Chuan; Adiana Ghazali,; Roswati Md Amin,; Kesaven Bhubalan,; Lee, Jen Nie; Tuan Mohamad Fauzan Tuan Omar,; Idham Khalil,; Suvik Assaw,; Yong, Jaw Chuen; Nurulnadia Mohd Yusoff,; Izan Jaafar,; Wan Nurul Nadiah Wan Rasdi,; et al. (Penerbit Universiti Kebangsaan Malaysia, 2021)
In December 2019, a novel coronavirus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak was reported for the first time in Wuhan, Hubei province, China. This coronavirus has been referred as Coronavirus Disease 2019 or COVID-19 by World Health Organization (WHO). The spread of COVID-19 has become unstoppable, infecting around 93.5 million people worldwide, with the infections and deaths still increasing. Today, the entire planet has changed due to the greatest threat on the planet since the introduction of this lethal disease. This pandemic has left the world in turmoil and various measures have been taken by many countries including movement control order or lockdown, to slow down or mitigate the infection. Since the lockdown has been implemented almost in all affected countries, there has been a significant reduction in anthropogenic activity, including a reduction in industrial operations, vehicle numbers, and marine-related activities. All of these changes have also led to some unexpected environmental consequences. As a result of this lockdown, it had a positive and negative impact on the environment including the aquatic environment. Hence this review will therefore focus on the good and bad perspectives of the lockdown toward the aquatic environment.